Kearifan Lokal Dalam Bidang Ekonomi Pada Masyarakat Nelayan (Studi Kasus: Desa Jaring Halus, Kecamatan Secanggang, Kabupaten Langkat) - Serli Andrianti; Mustapa Khamal Rokan (Universitas Islam Negeri Alauddin Makassar, 2022)
The purpose of this study was to determine the relationship and influence of labor, capital, technology and local wisdom variables on the income of fisherman in Jaring Halus Village, Langkat Regency. The method used in this research is quantitative, namely correlation test and multiple linear regression. The results of this study are the labor correlation value of 0.081 indicating no relationship, the capital correlation value of 0.521 indicating a moderat relationship, the technology correlation value of 0.483 indicating a moderate relationship, and the local wisdom correlation value of -0.198 meaning that there is no relationship. One of the factors causing the low income of fisherman in Jaring Halus Village is the low liquidity of fisherman and fishing gear that still use traditional tools. That the independent variables jointly affect the dependent variable.